I-FABP Is Higher in People With Chronic HIV Than Elite Controllers, Related to Sugar and Fatty Acid Intake and Inversely Related to Body Fat in People With HIV. (5th November 2018) - Cheru, Lediya T; Park, Elli A; Saylor, Charles F; Burdo, Tricia H; Fitch, Kathleen V; Looby, Sara; Weiner, Jeffrey; Robinson, Jake A; Hubbard, Jane; Torriani, Martin; Lo, Janet
Abstract: Background: Intestinal fatty acid binding protein (I-FABP) has been shown to be a marker of intestinal damage among people living with HIV. We hypothesized that I-FABP would be increased in chronically HIV-infected patents more than elite controllers and would relate to specific nutrient intake and body composition. Methods: In an observational study, serum I-FABP was measured by enzyme-linked immunosorbent assay. Anthropometric measurements, dual-energy x-ray absorptiometry, and single-slice abdominal computed tomography were obtained to assess body composition, as well as visceral and subcutaneous adipose tissue areas (VAT and SAT). Dietary intake was assessed using 4-day food records. Results: One hundred forty-nine people with chronic HIV (65% male, 47 ± 7 years of age, 54.7% white, and 14 ± 6 years of known HIV), 10 elite controllers (60% male, 53 ± 8 years, 60% white, and 20 ± 7 years of known HIV), and 69 HIV-negative controls (59.4% male, 46 ± 7 years, and 52.2% white) were included in the analysis. I-FABP was significantly higher in HIV progressors relative to HIV-negative controls and elite controllers. In the chronic HIV group, I-FABP was positively associated with dietary intake of added sugar and with saturated fatty acids. I-FABP was inversely associated with body mass index, VAT, and SAT. I-FABP also correlated with MCP-1, CXCL10, sCD163, and lipopolysaccharide (LPS) among all participants. Conclusions: I-FABP was increased among chronically HIV-infected patients to a greater degree than in elite controllers and was related to nutrient intake and body composition in HIV progressors. Future studies to investigate the role of intestinal damage on nutrient absorption are needed to elucidate the mechanisms of these relationships. Trial Registration Identifier: NCT00455793.